Economic analysis of venture activity at the venture enterprises - Pashkevych, Maryna; Usatenko, Olga (Technology audit and production reserves, 2017)
The modern methods of economic analysis with the help of which it is possible to analyze a venture activity for each stage of venture enterprise life cycle are analyzed in the article. The implementation of economic analysis as a fundamental factor in increasing the efficiency of venture activity of the venture enterprise has a significant impact on the effectiveness of risky activities and contributes to its main goal – to maximize profits. The venture management process proves that analysis is not only an integral part of other functions, but also an independent function. The effectiveness of venture activity at all stages of venture enterprise life cycle depends on the results of this function. The stages of life cycle are characterized by different degrees of risk and requirements in venture capital. The methods of analysis determined in the article take into account the features of each stage, the degree of risk, the need for investment and will avoid errors in plans and management decisions, choose the right strategy for planning, production, with the corresponding output volumes that will provide the desired volume of sales and financial results – satisfying both owners of venture enterprises and their risky investors.